Targeting the Ras superfamily via their regulatory GEF complexes - Gray, J (2021)
The Ras superfamily of small GTPases are guanine nucleotide-dependent molecular switches which are involved in numerous signalling pathways in the cell. Mutations or dysregulation of these proteins are associated with a variety of diseases, and so the small GTPases are important targets in drug discovery. Extensive medicinal chemistry efforts have largely been unsuccessful due to the difficulty in developing inhibitors to compete with GDP or GTP in an analogous manner to the ATP-competitive inhibitors of kinases. The activation of the small GTPases is regulated by guanine nucleotide exchange factors (GEFs). This thesis describes the efforts to identify small molecules which could be developed into novel inhibitors of the small GTPases by targeting their regulatory GEF complexes.